Speaking rate control based on time-scale modification and its effects on the performance of speech recognition. (1st January 2014) - Kang, Jin Ah; Choi, Seung Ho
In this paper, we describe the influence of speaking rate on speech recognition. Speaking rate of input speech is controlled by applying a time-scale modification (TSM) algorithm and speaking rate normalisation is achieved by selecting a scale factor of TSM. The scale factor selection for training and testing of a speech recognition system is performed based on a maximum likelihood criterion during HMM decoding. From the experimental results, we showed that optimal selection of a TSM scale factor in speaking rate normalisation can reduce WER by 47.6% compared to the baseline.